HUBUNGAN POLA MAKAN IBU, LAMA DAN FREKUENSI MENYUSUI DENGAN STATUS GIZI BAYI YANG DIBERIKAN ASI EKSKLUSIF DI WILAYAH KERJA PUSKESMAS PERUMNAS KADIA KOTA KENDARI - Amiruddin Amiruddin; Muhammad Sirih; Tyas Handayani Jamal (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2022)
Based on field observation, particularly in the working areas of Puskesmas Parumnas Kadia City of Kendari, it was found that breastfeeding mothers tend to have malnutrition babies. The study aimed to find out the correlation of mother's dietary, breastfeeding duration and frequency with infants nutritional status who received exclusive breastfeeding. The study was a correlational model which applied cross-sectional design and took 74 numbers of respondents. The study applied purposive sampling which came up with 74 respondents (total sampling). Result of the study found that mothers in a good diet category was 94,6 %, moderate category was 5,4 % and none of the bad diet category. High category of breastfeeding duration was 31,1 %, moderate was 64,9 % and low category was 4,1 %. Furthermore, the high category of breastfeeding frequency was 90,5 %, moderate was 89,5 % and none of the low category. Oversize nutritional status was not found, normal size was 98,6 %, and bad status was 1,4 %. Results of data analysis through Spearman correlation concluded that mother’s dietary, breastfeeding duration and frequency significantly correlate to infants’ nutritional status who received exclusive breastfeeding (p < 0.05).